Modeling and motion analysis of the MARES autonomous underwater vehicle - Bruno Ferreira (2009)
In the robotic domain, it is common to deduce and use models that allow translating mathematically the element behavior. In some cases, these would serve as base to determine and develop a controller, for example. Beyond this, the simulation and experiments are reasons that leave to the development of models, becoming evaluation tools of the system behavior, especially when there are constraints of implementation or in experiments. However, the modeling is an approach to the reality, since it is difficult to translate the behavior of an element in a strict way and the disturbances to witch it is subject to. In this work, we address the modeling questions of an autonomous underwater vehicle. This paper describes the deducing of a dynamic model with six degrees of freedom of an underwater vehicle, considering all of its physical characteristics. This is achieved by the determination of all forces that actuates on the body during its motions and by the determination of the rigid body dynamic. The modeling method is presented as well as the coefficients determination. Finally, a comparison with experimental results is carried out.